Implementasi Peraturan Pemerintah Nomor 79 Tahun 2013 Tentang Jaringan Lalu Lintas dan Angkutan Jalan Mengenai Batas Kecepatan Kendaraan Dijalan Tol Perspektif Fiqh Siyasah - Ari Yudha Fadhilah Nastan; Syaiful Amri (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The speed limit for vehicles on toll roads has been regulated by the government, its implementation has been stated in government regulation number 79 of 2013 in article 23 paragraph (4) part (b) which states that the minimum speed is 60 (sixty) kilometers per hour in free flow conditions and a maximum of 100 (one hundred) kilometers per hour for freeways. This research aims to see the extent to which vehicle speed limits are implemented on toll roads based on government regulations from a fiqh siyasah perspective. This research uses a normative juridical and empirical juridical approach with data sources namely primary data sources and secondary data sources. This research approach method is through the Statute Approach, Conceptual Approach and Case Approach. The results of this research and discussion explain that the application of Government Regulation Number 79 of 2013, namely article 23, for toll road drivers is still ineffective because there are still many drivers who violate the law regarding the speed limit of their vehicles when on toll roads. The implementation of government regulations regarding traffic networks and road transportation regarding vehicle speed limits on toll roads is actually in accordance with the Shari'ah, namely Fiqh Siyasah, especially Siyasah Dusturiyah, where we can see the collective benefit from the provisions on using toll roads as roads for motorists who drive and follow government regulations and uphold the rights of other motorists. If it is not implemented, it will not only violate government regulations, it will also violate the Shari'ah in accordance with the provisions of Fiqh Siyasah, especially Siyasah Dusturiyah.